Biotechnological description of technologies for obtaining of antigens of Candida genus fungi - Rybalkin М (Annals of Mechnikov’s Institute, 2020)
To develop the vaccine against candidal infection the various biotechnological methods for obtaining antigens of Candida genus fungi have been considered in the article. To obtain antigens for the prevention and treatment of candidiasis researchers use different types and parts of fungi of the genus Candida. Methods of preparation of antigens also vary widely including chemical, physical and physico-chemical techniques. Of all possible variants development and research of a dead and subunit vaccine based on C. albicans and C. tropicalis fungi that are the main causative agents of candidiasis have been chosen for further study.